ESTIMASI PARAMETER BERDISTRIBUSI PARETO MODEL SURVIVAL DENGAN METODE BAYESIAN PRECAUTIONARY LOSS FUNCTION - Ridhatul Ilahi; Ferra Yanuar; Dodi Devianto (LPPM Universitas Bina Bangsa, 2024)
The aim of this research is to determine the estimation of the scale parameters (θ) of a Pareto distributed survival model with known shape parameters (λ) using the Bayesian Precautionary Loss Function method using the Gamma prior. The data used in this research is secondary data in the form of data on the length of stay for Coronary Heart Disease patients from January 2023 - August 2023 obtained from M. Zein Painan Regional Hospital. Estimation of survival function parameters with the Bayesian Precautionary Loss Function method from the Pareto distribution using Gamma priors obtained and the value of the survival function with the Bayesian Precautionary Loss Function method calculates the chances of living in cases of Coronary Heart Disease sufferers to be higher. And will be evaluated using the AIC and BIC methods